Classification of Terms by Parts of Speech Affiliation - Mikayelyan, Karine (Bulletin of Yerevan University B: Philology, 2022)
Thus. 1. The principle of template classification of terms by parts of speech proposed above, as far as we know, is clearly formulated for the first time in linguistics as such. It makes it possible to consider terms in the totality of word-combination and morphological features, taking into account word-formation, semantics-semantic, morphological features of speech and figuratively-changing phenomena according to the above templates and formulas, that is, it is possible to conduct an examination of terms at the multivalued, phonetic, word-formation levels. 2. Equivalences of terms should also be generalized in industry terminological dictionaries with the inclusion of intra-system and multi-system terminological units, while they may also include units of different values covered by the word and term.